Adding Sodium–Glucose Co-Transporter 2 Inhibitors to Sulfonylureas and Risk of Hypoglycemia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jiang, Meng; Liu, Qiaoshu; Jiang, Tiejian; Nizigiyimana, Paul; Lei, Minxiang (Frontiers in Endocrinology, 2021)
Background: Hypoglycemia is an important event that could be related to increased mortality in patients with diabetes. The risk of hypoglycemia isn’t clearly illustrated to increase when Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are used concomitantly with sulfonylureas. The present study will assess the risk of hypoglycemia associated with the concomitant use of Sodium-glucose co-transporter 2 (SGLT-2) inhibitors and sulfonylureas compared with placebo and sulfonylureas. Method: We searched Medline, EMBASE, Cochrane Central Register of Controlled Trials, and Clinicaltrial.gov and identified the randomized trials comparing SGLT-2 inhibitors with placebo for type 2 diabetes treated with sulfonylureas. The risk of bias in each trial was assessed using the Cochrane tool. The risk ratio of hypoglycemia was measured using the Mantel Haenszel method. We also performed subgroup analysis to examine the dosage effects. The number needed to harm (NNH) was measured according to the duration of intervention. Results: A total of 12 studies, including 3761 participants, were enrolled in our systematic review and meta-analysis. The risk ratio of hypoglycemia was 1.67 (95% CI 1.42 to 1.97). The NNH was 13 (95% CI 9 to 21) for a treatment duration of 24 weeks or less, 11 (8 to 18) for 25 to 48 weeks, and 7 (5 to 10) for more than 48 weeks. Subgroup analysis showed that no difference was found between higher and lower doses of SGLT-2 inhibitors. The risk ratio related to lower dose SGLT-2 inhibitors was 1.56 (95% CI 1.30 to 1.88), and the risk ratio related to higher dose SGLT-2 inhibitors was 1.70 (95% CI 1.42 to 2.04). Conclusions: The risk of hypoglycemia was significantly increased in subjects treated with SGLT-2 inhibitors compared with placebo. Addition of SGLT-2 inhibitors to sulfonylureas would lead to one more case of hypoglycemia in every 13 patients with a treatment duration less than 24 weeks. This suggests that a decrease in sulfonylureas dose is important when adding SGLT-2 inhibitors to sulfonylureas.